Study guide [for] A people and a nation. - Norton, Mary Beth. (Houghton Mifflin, 1998)
Reconstruction: a partial revolution, 1865-1877. The development of the West and South, 1865-1877. The machine age, 1877-1920. The Vitality and Turmoil of urban life, 1877-1920. Gilded age politics, 1877-1900...